Innovative ICT-based strategies used by teachers for the development of social competences in business administration students. (2022)
This study is developed with the aim of diagnosing the innovative strategies based on ICT used by teachers for the development of social skills in business administration students; which were applied during the COVID 19 pandemic as a response to the change of modality launched by higher education institutions. In this case, the present study was located in the positivist paradigm, with a descriptive level, with a non-experimental, transactional field design. The sample is taken from a group of 25 teachers, who teach in the business administration program of a private university located in the city of Barranquilla, Colombia. A questionnaire consisting of a total of 15 items applied to this sample, which was validated by experts and its reliability was determined by means of the Cronbach's Alpha coefficient, yielding a value of 0.87. As a result, an average of 2.86 was obtained in the variable strategies for the development of social competences; located in the category neither appropriate nor inappropriate. These results show an important level of shortcomings in the implementation of innovative strategies based on ICT used by teachers for the development of social skills in business administration students